2002
DOI: 10.1080/15227950290097624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Modification on the Pharmacokinetics and Biodistribution of Carboxymethyl Dextran as a Drug Carrier

Abstract: The in vivo fate of drugs conjugated to macromolecules inevitably depends on that of macromolecules. However, the in vivo fate of macromolecules also may be altered by conjugation to drugs. For the efficient design of carboxymethyldextran (CMD) conjugates of a new analgesic drug, DA5018, we investigated whether the chemical modifications alter the pharmacokinetics and tissue distribution of CMD itself. [(14)C]CMD, oxidized [(14)C]CMD ([(14)C]OCMD), [(14)C]OCMD conjugates of DA5018 ([(14)C]OCMD-DA5018) and [(14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…It was previously reported that the tissue distribution of the CMD polymer and its derivatives bearing high molecular weights is higher in the kidneys, lungs and spleen [23,37]. The fluorescence intensities of the kidneys and spleen of mice injected with the CMD-s-s-peptide conjugates in this study were greater than those of mice treated with peptide alone, and may correspond to the tissue distribution of the CMD polymer; however, further investigations are needed to elucidate these suggestions.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…It was previously reported that the tissue distribution of the CMD polymer and its derivatives bearing high molecular weights is higher in the kidneys, lungs and spleen [23,37]. The fluorescence intensities of the kidneys and spleen of mice injected with the CMD-s-s-peptide conjugates in this study were greater than those of mice treated with peptide alone, and may correspond to the tissue distribution of the CMD polymer; however, further investigations are needed to elucidate these suggestions.…”
Section: Discussioncontrasting
confidence: 52%
“…We could remove the peptide-s-s-peptide by centrifugation method, but it is hard to remove completely the CMD-s-s-CMD from CMD-s-s-peptide conjugate. However, it is known that the CMD polymer itself is non-toxic [23], and thus it is suggested that the CMD-s-s-CMD in conjugate has no influence on both cytotoxic and anti-tumor activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More precise control could be gained by introducing magnetic nanoparticles, surface chemical modification, and biorelevant ligands (oligosaccharides, antibodies, polypeptides, viral proteins, etc.) to ENVs. …”
Section: Envs For Delivery Of Phytochemicalsmentioning
confidence: 99%
“…Owing to its biocompatibility and biodegradability, dextran and its derivatives have been widely investigated for biomedical applications such as drug delivery and tissue engineering . Carboxymethyl dextran (CMD) is one of the emerging derivatives for drug delivery applications because it has multiple functional groups including carboxyl, hydroxyl, and aldehyde groups, allowing for facile chemical modification . In this study, we developed a polymeric conjugate with a pH‐sensitive ester linkage between CMD and DTX as a drug carrier for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%